ANALISIS PENGARUH GENDER, KECERDASAN EMOSIONAL DAN IDEALISME PADA PERSEPSI ETIS MAHASISWA AKUNTANSI - Niken Intan Syabilla; Muslimin Muslimin (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Every profession must work professionally, especially for accountants, it is very necessary to have an ethical nature to carry out their work. Many cases of violation of professional ethics by accountants, lead adverse impact on sense on the performance of an accountant. This study aims to determine, examine and analyze the effect of gender, emotional intelligence and idealism, on ethical perception of accounting students. This type of research uses quantitative approach. Primary data is taken from questionnaires distributed to respondents of Accounting Students of Universitas Pembangunan Nasional “Veteran” Jawa Timur dan Universitas Islam Negeri Sunan Ampel Surabaya class of 2017-2018 with slovin’s formula for determining the number of samples. Statistical analysis method used multiple regressions linier. The results of the study were obtained that gender has been proven to have a positive and significant effect on ethical perception of accounting students, emotional intelligence has been proven to have a positive and significant effect on ethical perception of accounting students, and idealism has been proven to have a positive and significant effect on ethical perception of accounting students. Keywords: Gender, Emotional Intelligence, Idealism, Ethical